Microstructural Characterization of Carbon Nanotubes (CNTs)-Reinforced Nickel Matrix Nanocomposites. (24th September 2018) - Simões, Sónia; Carneiro, Íris; Viana, Filomena; Reis, Marcos A. L.; Vieira, Manuel F.
Abstract: This research focuses on the microstructural characterization of nickel matrix composites reinforced by carbon nanotubes (CNTs). The nanocomposites were produced by a conventional powder metallurgy process and the dispersion of CNTs and mixture with nickel powders was performed in a single step by ultrasonication. Microstructural characterization of Ni–CNT nanocomposites was performed by scanning and transmission electron microscopy, electron backscattered diffraction, high-resolution transmission electron microscopy, selected area electron diffraction, and fast Fourier transform analyses. This characterization revealed CNTs embedded in the nickel grains and mainly presented as clusters at the grain boundaries. CNTs hinder recrystallization during sintering, and dislocation cells and subgrains form as a result of the recovery process.